2018
DOI: 10.1080/10407782.2018.1543920
|View full text |Cite
|
Sign up to set email alerts
|

Convergence angle and dimple shape effects on the heat transfer characteristics in a rotating dimple-pin fin wedge duct

Abstract: A numerical method is employed to study effects of convergence angle and dimple shape on flow structure and heat transfer under a rotating frame. The investigated convergence angles are 0.0 , 6.3 , and 12.7. The dimple shapes are circular, streamwise-elliptical, and spanwise-elliptical. The rotation number ranges from 0.0 to 0.4. Computed flow structures and heat transfer are compared. Higher rotation number generates better heat transfer in the dimple-pin wedge duct. The rotation direction also affects the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Based on the above discussion, realizable k-ε turbulent model shows the best agreement with experimental results under both stationary and rotating conditions. In addition, previous studies (Du et al , 2019; Luo et al , 2018; Yan et al , 2021) also acknowledged that realizable k-ε turbulent model shows the better ability of accurately capturing and evaluating the heat transfer enhancement and friction loss of pin fin-dimpled channels. Thus, realizable k-ε turbulent model combined with enhanced wall function is chosen.…”
Section: Computational Methods and Proceduresmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on the above discussion, realizable k-ε turbulent model shows the best agreement with experimental results under both stationary and rotating conditions. In addition, previous studies (Du et al , 2019; Luo et al , 2018; Yan et al , 2021) also acknowledged that realizable k-ε turbulent model shows the better ability of accurately capturing and evaluating the heat transfer enhancement and friction loss of pin fin-dimpled channels. Thus, realizable k-ε turbulent model combined with enhanced wall function is chosen.…”
Section: Computational Methods and Proceduresmentioning
confidence: 96%
“…As shown in Figure 2, the endwalls, dimples and pin fins are applied with q = 1,000 W/m 2 wall heat flux (Du et al , 2019; Luo et al , 2018). All the walls are viewed as no-slip wall.…”
Section: Computational Methods and Proceduresmentioning
confidence: 99%
“…However, the temperature of the superheated steam leaving the pressure reducing valve should be reduced. In order to augment the heat transfer efficiency, scholars have proposed many novel high-efficiency heat transfer devices like spirally corrugated tube [6][7][8], dimpled surfaces [9][10][11], and inserted tubes/microtubes [12,13]. Furthermore, many investigators aimed at conducting research on the cooling of superheated steam.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of heat transfer and flow resistance for five types of LVGs were studied numerically at the Reynolds number range of Re ¼ 8,900-29,900 by Xu et al [25]. Luo et al [26] numerically studied the effects of convergence angles and dimple shapes on flow structure and heat transfer characteristics in a rotating dimple-pin fin wedge duct. The results indicated that the spanwise-elliptical dimple shape offered the best heat transfer augmentation as it generated the strongest vortex structure and turbulent kinetic energy in the dimples, and larger convergence angles exhibited larger Nusselt numbers and better heat transfer enhancement.…”
Section: Introductionmentioning
confidence: 99%